IN VITRO SCREENING OF ANTIBACTERIAL AND ANTIOXIDANT ACTIVITY AND IN SILICO ANALYSIS OF THREE SIDED CISSUS QUADRANGULARIS - J. HELAN CHANDRA; SUHASHINI. R (International Journal of Pharma and Bio Sciences, 2015)
The present study is to screen the antibacterial and antioxidant activity of the plant three sided Cissus quadrangularis (Muppirandai) and to perform in silico analysis for the compounds identified through GC-MS analysis. Ethanolic extract of the plant was prepared by soxhlet extraction. Antibacterial activity was tested against Bacillus cereus, Staphylococcus aureus, Escherichia coli and Salmonella typhi, among which the extract was more effective against Staphylococcus aureus. Phytochemical analysis proved the presence of constituents such as flavonoids, carbohydrates, tannins, phenols, saponins, proteins and amino acids. Antioxidant potential of the plant was evaluated by DPPH assay. Nine compounds were identified through GC-MS analysis and were subjected to docking study, which was performed with LuxS receptor 1JVI using Autodock 4.2, Cygwin and Discovery studio. These compounds exhibited high negative binding energy and a maximum of three hydrogen bonds were formed between the ligand Cholestane-3, 6, 7-triol, (3à, 5à, 6à, 7à) and the receptor.